HUBUNGAN KONSUMSI PANGAN SUMBER KALSIUM DAN AKTIVITAS FISIK DENGAN KEPADATAN TULANG LACTO OVO VEGETARIAN DI YAYASAN BUDDHA TZU CHI SURABAYA - Intan Sekar Putri Nugroho; Lailatul Muniroh (Media Gizi Indonesia, 2017)
Vegetarian is one of dietary pattern that is believed to prevent degenerative diseases, but vegetarian apparently can  lower calcium absorption due to the high intake of oxalic and phytate acid that can reduce bone density. Physical activity can also affect the bone density. Intense physical activity will make bone density stronger. The purpose ofthis study was to analyze the correlation between consumption of calcium food sources and physical activity with bone density of lacto ovo vegetarian at Buddha Tzu Chi Surabaya Foundation. This research was an observational analytic, using cross sectional study design. The sample were 31 adult, taken through the inclusion criteria of alacto ovo vegetarian, a vegetarian diet ≥ 1 year, age ≥ 20 years old. Data collection through measurement of Bone Mineral Density (BMD) using bone densitometry Quantitative Ultrasound (QUS) method, interview of respondent characteristics, consumption of calcium food sources by Semi Quantitative Food Frequency Questionnaire (SQ-FFQ), and physical activity by International Physical Activity Questionnaire (IPAQ). The data was analyzed using Pearson Test. The results showed that there was a correlation between consumption of calcium food sources (p = 0.000) and physical activity (p = 0.022) with bone density of lacto ovo vegetarian. The higher consumption of calcium food sources and physical activity can increase bone density. Respondents should increase physical activity and doing routine exercise to make bone density stronger, and consume high calcium of foods such as broccoli, pokcoy, orange, and cow’s milk.